Morphological and immunohistochemical features of deobliterated femoral arteries and saphenous veins of patients with obliterating atherosclerosis of the lower extremities vessels in conditions of critical ischemia - I. S. Shpon'ka; O. L. Tkachuk; O. I. Gudz; O. V. Poslavs'ka (Zaporozhye State Medical University, 2013)
Introduction. Reconstructive surgery for atherosclerosis of the aorta and major arteries rapidly entered the offices of the daily practice of vascular surgery, due to the improved quality of life for patients in this age group. It should be noted that in almost half of patients with obliterating atherosclerosis (OA) in the performance of arterial reconstruction the great saphenous vein (GSV) appears unsuitable for its use as vein transplant. In such cases, for saving the limb synthetic material is used, which functions for a brief period due to non-compliance properties with the arterial wall. In recent years, for the prevention of stenosis rapid development in the area of sewing transplant to the tibial or popliteal arteries using venous insertions is suggested. However, in practice, quite often in these patients it is impossible to find even a short (5-10cm) venous segment to implant it between transplant and vein. In contrast, own desobliterated femoral artery (removal stenosis cylinder to internal or external elastic membrane) with appropriate anticoagulation drug support may be an interesting option for implantation in patients without adequate GSV. The purpose of this qualitative study was to assess the impact of desobliteration (to internal or to external elastic membrane) on the vascular matrix and antithrombotic properties of the wall of the femoral artery, compared with the great saphenous vein. Materials and Methods. Material of 21 male patients aged 50 to 73 years was studied, the total group of desobliterated femoral arteries (DFA) included two groups: the first - the DFA to the internal elastic membrane (n=8) and the second - DFA to the external elastic membrane (n=7). The control group consisted of 6 pieces of GSV. Primary monoclonal antibodies CD31, Ki-67, Collagen IV, aSM-1, Myosin, Desmin, MMP-9, TIMP-1 were used. Statistical analysis of data was carried out in the program SPSS Statistica 17.0. To establish a statistically significant relationship between the clinical and morphological features and the expression of markers nonparametric U-Mann-Whitney was used. Comparison of mean values was carried out using Student's criteria. A significant relationship was considered at p<0.05. Results and Discussion. In the study of DFA fragments compared with GSV we were interested in two main questions: morphology of obtained "through-tubing" that in the absence of the intimal and smooth muscle layers in contact with collagen contributed to early complications - thrombosis and remote narrowing of the lumen of the graft anastomosis in the area due to proliferation of the smooth muscle component of the vessel wall. Conclusion. GSV, despite the presence of the endothelium compared with DFA has intimal fibrosis and hypertrophy of the longitudinal and circular muscle with a significant increase in media type IV collagen. More rigid structure in I group tube wall (p<0.05) and increased risk of intramural hematoma in group II due to the large vascularization (p<0.05) and low strength are noted. Both DFA groups had equally low background for hyperplasia of smooth muscle cells, as compared to the GSV (p<0.05) and the high risk of thrombosis due to desobliteration (p<0.05). In the context of multifocal atherosclerosis with severe fibrosis of vessel walls expression level of MMP-9, aimed at the degradation of type IV collagen, is equally high in all three study groups (p>0.05).